GSK3-beta as a candidate therapeutic target in soft tissue sarcomas - S. Verbeke (BMC, 2021)
Abstract Soft tissue sarcoma (STS) is a predominantly fatal rare malignancy with inadequate treatment options. Glycogen synthase kinase 3β (GSK-3β) is an emerging target in human malignancies. Its therapeutic relevance in STS is unknown. We analyzed the prognostic impact of GSK-3β gene and protein expression in two independent cohorts of patients with STS. We then treated STS cell lines and mice xenografts with a novel GSK-3 inhibitor 9-ING-41 alone or in combination with chemotherapy. We demonstrated that 9-ING-41 treatment induced significant STS cells apoptosis and was synergistic in vivo when combined with chemotherapy. Mechanistically, 9-ING-41 induces significant apoptosis of STS cells via suppression of NF-κB-mediated X-linked inhibitor of apoptosis protein (XIAP) expression. These data support the inclusion of patients with STS in clinical studies of 9-ING-41 alone and in combination with chemotherapy.